Застосування ізотропної та анізотропної концепцій пошкоджуваності до розрахунку тривалої міцності ротору парової турбіни в умовах високотемпературної повзучості - Гораш, Є. М. (НТУ "ХПІ", 2006)
Within the framework of the research work two typical material models describing isotropic and anisotropic creep-damage processes in metals and alloys are applied to the simulation of the mechanical behaviour of a steam turbine rotor in its service conditions. Numerical solutions of the initial-boundary value problems have been obtained by FEM using solid axisymmetrical type finite elements. For the purpose of adequate long-term strength analysis both isotropic and anisotropic creep-damage models have been implemented in FE-code of the universal CAE ANSYS. Obtained simulation results for a steam turbine rotor show the significant sensitivity of life-time assessment to the type of material model
Keywords: механіка пошкоджуваності суцільного середовища; тонкостінні конструкції; ізотропна модель повзучості; анізотропна модель повзучості; парова турбіна